2011
DOI: 10.3233/jad-2010-100894
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Laser Therapy Attenuates Amyloid-β Peptide Neuropathology in Amyloid-β Protein Precursor Transgenic Mice

Abstract: Transcranial laser therapy (TLT) was tested for efficacy in a mouse model of Alzheimer's disease (AD) using a near-infrared energy laser system. TLT is thought to stimulate ATP production, increase mitochondrial activity, and help maintain neuronal function. Studies were performed to determine the effect of TLT in an amyloid-β protein precursor (AβPP) transgenic mouse model. TLT was administered 3 times/week at various doses, starting at 3 months of age, and was compared to a control group (no laser treatment)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
188
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(195 citation statements)
references
References 50 publications
6
188
0
1
Order By: Relevance
“…They found that LLLT treatment decreases Aβ plaques and the expression of inflammatory markers in the AβPP transgenic mice [10]. In addition, LLLT treatment showed an increase in ATP levels, mitochondrial function, and c-fos, which result in an overall improvement in neurological function [10]. The data suggest that LLLT is a potential candidate for treatment of AD.…”
Section: Lllt Is Involved In Regulation Of Oxidative Stress and Anti-mentioning
confidence: 95%
See 3 more Smart Citations
“…They found that LLLT treatment decreases Aβ plaques and the expression of inflammatory markers in the AβPP transgenic mice [10]. In addition, LLLT treatment showed an increase in ATP levels, mitochondrial function, and c-fos, which result in an overall improvement in neurological function [10]. The data suggest that LLLT is a potential candidate for treatment of AD.…”
Section: Lllt Is Involved In Regulation Of Oxidative Stress and Anti-mentioning
confidence: 95%
“…De Taboada et al tested whether LLLT plays an anti-inflammation role in an Aβ protein precursor (AβPP) transgenic mouse model, a mouse model of AD [10]. They found that LLLT treatment decreases Aβ plaques and the expression of inflammatory markers in the AβPP transgenic mice [10]. In addition, LLLT treatment showed an increase in ATP levels, mitochondrial function, and c-fos, which result in an overall improvement in neurological function [10].…”
Section: Lllt Is Involved In Regulation Of Oxidative Stress and Anti-mentioning
confidence: 99%
See 2 more Smart Citations
“…Esta terapia vem crescendo no campo do derrame cerebral (170,171) , injuria traumática do cérebro (172)(173)(174) , doenças neurodegenerativas (175) , e lesões de medula espinal (176) .…”
Section: Laser Em Baixa Intensidadeunclassified